The EFFECT OF BRAND SALIENCE AND BRAND RESONANCE ON CONSUMER LOYALTY TOWARDS LOCAL FASHION BRANDS IN INDONESIA - Linanda, Pratika; Fenisa, Delta; Aryasa, Hence Made; Adiananta, Bayu Fahmi (Journal of Business Studies and Management Review, 2025)
In this increasingly fierce competitive landscape, local Indonesian fashion brands face the challenge of building strong brand resonance, especially among Gen Z consumers. Brand resonance, as defined by Keller (2013), refers to a deep connection between consumers and brands, which is characterized by active and intense loyalty. One of the key factors in building brand resonance is through brand salience, which refers to the extent to which a brand appears in consumers' minds in various purchasing and consumption situations (Romaniuk & Sharp, 2020). Generation Z in Indonesia is a very important consumer segment for the fashion industry. According to research conducted by Nielsen (2020), Gen Z in Indonesia represents around 27% of the total population and has significant purchasing power. A study by Deloitte Indonesia (2021) revealed that 62% of Gen Z Indonesia prefers local brands over international brands, indicating a huge opportunity for local fashion brands to develop. This study aims to explore the relationship between brand salience and brand resonance, and their effects on consumer loyalty towards local fashion brands in Indonesia.